Refugee women’s access to and use of emergency contraceptives as a reproductive health right in Kenya - Budoo-Scholtz, Ashwanee (University of Pretoria, 2024)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.